Comparison of Robotic and Manual Persistent AF Ablation Using Catheter Contact Force Sensing: An International Multicenter Registry Study. Issue 11 (15th September 2014) - ULLAH, WAQAS; HUNTER, ROSS J.; HALDAR, SHOUVIK; MCLEAN, AILSA; DHINOJA, MEHUL; SPORTON, SIMON; EARLEY, MARK J.; LORGAT, FAIZEL; WONG, TOM; SCHILLING, RICHARD J.
<x xml:space="preserve">Abstract</x> Background Catheter‐based contact force sensing (CFS) technology gives detailed information regarding contact between the catheter tip and myocardium. This may result in more effective ablation procedures. The primary objective of this study was comparison of remote robotic navigation (RRN) and Manual CFS ablation. The secondary objective was to compare CFS with non‐CFS ablation for both navigation modes. Methods Prospective registries of consecutive cases undergoing their first ablation for persistent atrial fibrillation (AF) from six hospitals in the United Kingdom and South Africa were analyzed: 50 Manual/CFS and 50 RRN/CFS cases were included. Historical control non‐CFS ablation patients were matched by propensity score, giving a total 200 patient cohort. Results RRN/CFS was associated with improved single procedure 1‐year success rates (64% vs 36%, P = 0.01) and shorter fluoroscopy times (41% reduction, P < 0.0005) than Manual/CFS ablation, without any difference in procedure times (P = 0.8). The mean contact force was higher in RRN/CFS than Manual/CFS cases (16 [15–18 g] vs 13 [12–15 g], respectively, P = 0.003). Compared with non‐CFS historical controls, CFS cases had higher 1‐year success rates for RRN (64% vs 36%, P = 0.01), but not Manual ablation (36% vs 38%, P = 1). Procedure times were reduced for CFS cases (20%, P < 0.005 both navigation modes), as were fluoroscopy times (Manual: 43%, RRN 83%, P < 0.005 for both). There were no differences in rates of major or minor complications for either comparison (P > 0.5). Conclusions A combination of RRN and CFS is associated with improved success rates at 1 year and fluoroscopy times for persistent AF ablation, compared with Manual ablation and non‐CFS RRN ablation.